Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1128/mbio.02267-21
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus UL138 Protein Inhibits the STING Pathway and Reduces Interferon Beta mRNA Accumulation during Lytic and Latent Infections

Abstract: While a cellular restriction versus viral countermeasure arms race between innate immunity and viral latency is expected, few examples have been documented. Our identification of the first HCMV latency protein that inactivates the cGAS/STING/TBK1 innate immune pathway opens the door to understanding how innate immunity, or its neutralization, impacts long-term persistence by HCMV and other latent viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 68 publications
0
17
2
Order By: Relevance
“…Contrary to our findings, Kalejta and colleagues showed that UL138 inhibits the innate immune response by targeting STING for degradation [41]. UL138 was shown to target STING, but this effect was only evident when both UL138 and STING were transiently overexpressed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, Kalejta and colleagues showed that UL138 inhibits the innate immune response by targeting STING for degradation [41]. UL138 was shown to target STING, but this effect was only evident when both UL138 and STING were transiently overexpressed.…”
Section: Discussioncontrasting
confidence: 99%
“…Given the reported roles of USP1 in stabilizing TBK1 [40] and of UL138 in targeting STING for degradation outside the context of infection [41], we analyzed total and phosphorylated levels of TBK1 and STING during HCMV infection. Phosphorylated and total levels of TBK1 and STING remained unchanged between WT and Δ UL138 STOP infections (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining defects in virus production are indicative of the above mentioned complexity of mitochondrial alterations caused by mito-RFP-ER upon infection (Supplementary Fig. 10E ), and the possibility of STING performing both pro- and anti-viral roles during HCMV infections 6 , 85 , 95 . Together with our other findings that mito-ER tethering causes STING relocalization, TBK1 and IRF3 phosphorylation, cytokine secretion, reduced virus gene expression, and delayed infection onset, our results demonstrate that the STING immune pathway is a contributor to the anti-viral effect of premature ER-mitochondria tethering.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have defined roles of UL133-138 gene locus encoded within the ULb' region of the HCMV genome for latency and reactivation. UL138 is required for latency and functions by regulating cell surface receptor trafficking and signaling (11)(12)(13)(14), innate immune responses (15) and also contributes to repression of viral gene expression (16). UL135, by contrast, is required for reactivation from latency, functioning in part by opposing the function of UL138 (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%